A comparative study between autologus blood injection and extensor tendon release for resistant tennis elbow - KAILASH S; MUTHUKUMAR K; VIJAYANARASIMHAN V (International Journal of Pharma and Bio Sciences, 2017)
Tennis elbow or lateral epicondylitis is a common condition affecting the active population. Various conservative and surgical modalities exist regarding treatment but there is no universal consensus regards to the individualising the management. In this study we compare the outcome of resistant tennis elbow cases treated with autologous blood injection and open surgical release. Both modalities of management gave encouraging results in resistant cases but no statistically significant difference between the two modalities. In resistant cases of tennis elbow, biological treatment accelerating the repair process (use of Autologus blood injection) should be considered before performing surgery.